Analisis Proses Berpikir Siswa dalam Menyelesaikan Soal HOTS Ditinjau dari Gaya Kognitif - Arnindia Via Mawardi; Aning Wida Yanti; Yuni Arrifadah (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2020)
The students’ thinking process when solving HOTS questions in mathematics National Examinations very necessary to know. There are three types of students’ thinking processes used in this study, namely conceptual thinking, semi-conceptual thinking, and computational thinking. This study aims to describe in detail about field-independent and field-dependent students' thinking process when solving HOTS questions in the 2018 Mathematics National Examination. The research subjects were six 8th grade students, consisting of 3 students on each cognitive style. Data collection techniques are written test and interview. The written test and interview results data are analyzed according to indicators of the thinking process. The results of this study indicate that the field independent students' thinking process is conceptual while dependent students are computational.